A novel full-scale external geothermal heating system for bridge deck de-icing. (25th February 2021) - Habibzadeh-Bigdarvish, Omid; Yu, Xinbao; Li, Teng; Lei, Gang; Banerjee, Aritra; Puppala, Anand J.
Highlights: A full-scale externally heated geothermal bridge deicing system was implemented. The bridge surface was above freezing and ice-free during all winter events. The average coefficient of performance of the deicing system was 4.6. The average surface heat flux of 236.2 W/m 2 was estimated during a winter test. Approximately 55% of the supplied heat was transferred to the bridge deck surface. Abstract: The utilization of geothermal energy for melting snow and ice on bridge decks has been shown to be effective. However, the existing geothermal heating systems work through hydronic loops embedded inside the bridge deck and therefore are only applicable to new bridges. A new external geothermal heating design for bridge de-icing has been explored in concept and tests in the laboratory, showing great implementation potential. This study presents the design and implementation procedure of a novel external geothermal heating system on a full-scale bridge deck for de-icing operations in field conditions for its first time. It tests and analyzes the system's heating performance and the bridge deck's thermal response under several winter events. The details and information pertaining to the design and construction of the hydronic loops, a ground loop heat exchanger (GLHE) monitoring system, are presented and can be pivotal for the designers of similar projects. The test results showed that the system was successful in de-icing the bridge deck and maintaining the bridge deck surface temperature above freezing in the event with a minimum ambient temperature of −6.2 °C. The de-icing system requires about 7–8 h of pre-heating to reach its maximum performance; however, less time is required during mild events. Moreover, this research investigated the performance of the system, and the experimental results showed an average system coefficient of performance (COP) of approximately 4.6 and a heating efficiency of about 55%.